Effect of roof and wall material on energy usage for house cooling system in hot-humid climate - Izzah A Wardah; Niken Adriaty Basyarach (University of Muhammadiyah Malang, 2022)
A model of a typical townhouse in Surabaya is simulated using building energy simulation software to analyse the energy consumption for cooling due to a severe climate. The assessment focused on the internal heat effects caused by the wall and roof material to meet the thermal comfort in a hot-humid climate region. A baseline building was a one-story building for one family with the typical load profile in Surabaya applied. The insulation thickness and material composition of the wall and roof were varied, whereas the internal cooling system was maintained at 25.5oC by the air-conditioning system. Results are presented and compared in terms of the annual energy consumption to meet the Indonesian standards for buildings. The best optimisation shows that the implementation of the insulation in the model can lower the annual energy consumption and conserve the energy by 37%.